THE INFLUENCE OF SELF-EFFICACY, ORGANIZATIONAL CULTURE, AND WORK MOTIVATION ON EMPLOYEE PERFORMANCE: EVIDENCE FROM BANK SULTRA RAHA BRANCH - Weldy Soemargo; La Hatani; Nursaban Rommy; Usman Usman (Journal Economics Technology And Entrepreneur, 2026)
This study aims to analyze the influence of self-efficacy, organizational culture, and work motivation on employee performance at Bank Sultra Raha Branch, both simultaneously and partially. The study employed a quantitative approach with an explanatory research design. All 46 employees of Bank Sultra Raha Branch were selected as respondents using the census sampling technique. Data were collected through structured questionnaires and analyzed using multiple linear regression. The findings indicate that self-efficacy, organizational culture, and work motivation simultaneously have a positive and significant effect on employee performance. Partially, each variable also demonstrates a positive and significant influence on performance improvement. These results suggest that strengthening employees’ self-confidence, fostering a supportive organizational culture, and providing continuous work motivation are essential factors in enhancing employee performance. Therefore, organizations should develop these three aspects in an integrated manner to achieve organizational objectives, improve service quality, and strengthen organizational competitiveness in an increasingly dynamic business environment.